A CASE OF ADULT VARIANT BARTTER SYNDROME - Ullah, Sami; Azam, Malik Nadeem; Khan, Zubair Waheed; Akhtar, Syed Muhammad Hassan (Pakistan Armed Forces Medical Journal, 2018)
Bartter syndrome was first described in an article by Bartter et al in 1962 [1]. Bartter syndrome is a rare genetic disease characterized by hypokalemia, alkalosis, and normal to low blood pressure. We describe it due to the rarity of the condition and because it was described once in our country and that too in a neonate [2] whereas our patient is an adult.